Five subglacial lakes and one of Antarctica's thickest ice covers newly determined by radio echo sounding over the Vostok-Dome C region - Cafarella, L.; Urbini, S.; Bianchi, C.; Zirizzotti, A.; Tabacco, I. E.; Forieri, A. (Blackwell Publishing, 2006)
Radio echo sounding (RES) measurements were collected from 1995 to 2003 during Italian Antarctic expeditions over the Vostok-Dome C region. The data collected allow for the reconstruction of a bedrock elevation map between the Belgica Highlands and the Aurora Subglacial Basin (112.0° - 124.0°E 74.0° - 78.0°S). Moreover, analysis of the RES data has revealed one of the thickest ice covers in Antarctica (4755 ± 16 m; 118.321°E, 76.059°S) as well as five new subglacial lakes. Published 69-73 3.8. Geofisica per l'ambiente JCR Journal reserved